The boys in the boat nine Americans and their epic quest for gold at the 1936 Berlin Olympics - Brown, Daniel 1951- (Viking, 2013)
This book tells the story of the University of Washington's 1936 eight-oar crew and their epic quest for an Olympic gold medal, a team that transformed the sport and grabbed the attention of millions of Americans. It traces the story of the team that defeated elite rivals at Hitler's 1936 Berlin Olympics, sharing the experiences of their enigmatic coach, a visionary boat builder, and a homeless teen rower